Experimental study on panel zone behavior of diaphragm-through connections to concrete-filled tube columns. Issue 1 (January 2020) - Wu, Liao
In order to verify the accuracy of the panel zone shear capacity calculation method of diaphragm-through connections which were proposed in previous research, the low cycle repeated load tests of six cross-shaped specimens were carried out. The seismic performance of the panel zone's stress distribution, failure mode, hysteresis curve, and skeleton curve are comprehensively studied and analyzed. The results showed that the steel tube web and core concrete were mainly participating to bear the horizontal shear force, and the "steel frame" composed of the steel tube flange and through-diaphragm was negligible for the shear resistance; the core concrete strut calculated width and height were all one-fourth of the height and width of the panel zone. The test results are in good agreement with the results of the calculation method, which indicated that the calculation method proposed in the previous research results had good accuracy and applicability, and would use for the panel zone shear capacity calculated in the connections design.